Study of The Judge's Considerationstothe Crime of Theft under Avery Circumstances (Study Decision Number 236/PID.B/2021/PN KLN) - Muhammad Ikhsan Rifai; Natangsa Surbakti (Proceeding International Conference Restructuring and Transforming Law, 2023)
The author of writing this journal aims to analyze and find out the problems in cases of theft committed by perpetrators. The Panel of Judges in implementing an element of the crime of theft in line with Article 363 paragraph (1) 3rd, 4 and 5 of the Criminal Codes. In the defendant's action it was proven valid and able to meet the elements, namely: Whoever, took something that is wholly or partly owned by another persons, the elements with the intention to own it by means of violating an applicable law, the action was carried out at night in the house, which then it was done by someone who was there who the owner did not know or wanted. Furthermore, the panel of judges stipulated a decision, namely, declared the defendant valid and could indicate that he was proven guilty when he committed the crime of theft under aggravating circumstances, because of this matter the defendant was valid and firmly guilty of the crimes of theft under aggravating circumstances; Sentenced the defendant 2 (two) years in prison.